Relating paradigms: what do transdisciplinary researchers need to know about interdisciplinary science?. (1st January 2001) - van Kerkhoff, Lorrae
Currently there is considerable talk about the need for transdisciplinary research, but few hints as to what this might be or how researchers might go about doing it. One way of trying to better understand transdisciplinarity and how to achieve it is to examine its predecessor, interdisciplinarity. In this paper some of the practical insights that emerge from the literature on interdisciplinary research that are relevant to attempts to relate different paradigms are outlined. It is suggested that these insights are insufficient to help researchers develop a transdisciplinary framework. One possible alternative way of approaching the development of such a framework, by using the social research technique of grounded theory, is discussed. By treating research as a social and political activity, rather than a strictly "scientific" one, it may be possible to develop a transdisciplinary framework that is also socially and politically relevant.